2008
DOI: 10.1271/bbb.80383
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Systematic Drug Screening Method Using Chemical Arrays and the Protein Library: Identification of Novel Inhibitors of Carbonic Anhydrase II

Abstract: The identification of specific interactions between small molecules and human proteins of interest is a fundamental step in chemical biology and drug development. Here we describe an efficient method to obtain novel binding ligands of human proteins by a chemical array approach. Our method includes large-scale ligand screening with two libraries, proteins and chemicals, the use of cell lysates that express proteins of interest fused with red fluorescent protein, and high-throughput screening by merged display … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The slides of Natural Products Depository (NPDepo ) ( 15 ) were prepared and analyzed as reported before (16)(17)(18). The microarray screening was performed using the following buffer: 20 mM Hepes, 150 mM NaCl, pH 7.53-7.55.…”
Section: Microarray Screeningmentioning
confidence: 99%
“…The slides of Natural Products Depository (NPDepo ) ( 15 ) were prepared and analyzed as reported before (16)(17)(18). The microarray screening was performed using the following buffer: 20 mM Hepes, 150 mM NaCl, pH 7.53-7.55.…”
Section: Microarray Screeningmentioning
confidence: 99%
“…Chemical arrays represent one of the most promising and high-throughput approaches for screening ligands against proteins of interest (Kanoh et al, 2006), and several successful results from chemical arrays have been reported (Koehler et al, 2003;Kuruvilla et al, 2002;Miyazaki et al, 2008). The screening protocol using chemical array was shown in Fig.…”
Section: Screening Of Anti-viral Drugs For Npmentioning
confidence: 99%
“…The platform consists of a chemical array that bears compounds deposited in the Natural Product Depository (NPDepo) 20) and the protein library generated from the Gene Library of the Osada Laboratory of RIKEN for chemical array analysis (GLORIA). 21) To use GLORIA for our chemical array system, we cloned 100 genes and engineered them to express a fusion between red fluorescent protein (RFP) 22) and the protein of interest. HEK293T cells were transfected with vectors that encoded RFP-fused proteins or RFP alone, and cell lysates were prepared.…”
Section: Chemical Arraymentioning
confidence: 99%
“…After merged display analysis, we identified two hit compounds. 21) To test the specificity of 1 and 2 for CAII, we prepared cell lysates from HEK293T cells that expressed 33 RFPfused proteins, including CAII, from GLORIA. Among the 33 proteins tested, only the cell lysate that expressed RFP-fused CAII interacted with 1 and 2, suggesting that 1 and 2 are selective inhibitors of CAII.…”
Section: Chemical Arraymentioning
confidence: 99%
See 1 more Smart Citation